2005
DOI: 10.2175/106143005x41627
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Macrolide‐Lincosamide‐Streptogramin B and Tetracycline Antimicrobials in Swine Waste Treatment Processes and Amended Soil

Abstract: Little is known about the fate of antimicrobials during common agricultural waste handling procedures. To better define the potential scope of this problem, concentrations of antimicrobials throughout the waste treatment process were estimated based on known antimicrobial usage, and the resulting predictions of high antimicrobial concentrations indicated the need for further investigation. Samples from building pits, a solids settling basin, a holding pond, and soil amended with waste treatment byproducts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 20 publications
0
27
1
Order By: Relevance
“…Antimicrobials added to animal feed are not completely absorbed during digestion, resulting in their presence in manure (Heuer et al, 2011). The presence and activity of antimicrobials in manure can select for antimicrobial resistant bacteria, even at low antimicrobial concentrations (Knapp et al, 2008) and antimicrobials, ARGs, and resistant bacteria can enter the environment through a variety of pathways including agricultural wastewater (Wantanabe et al, 2010;Zhang et al, 2013) or land applied animal manure (Zilles et al, 2005;Pei et al, 2006;Heuer et al, 2011;Joy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobials added to animal feed are not completely absorbed during digestion, resulting in their presence in manure (Heuer et al, 2011). The presence and activity of antimicrobials in manure can select for antimicrobial resistant bacteria, even at low antimicrobial concentrations (Knapp et al, 2008) and antimicrobials, ARGs, and resistant bacteria can enter the environment through a variety of pathways including agricultural wastewater (Wantanabe et al, 2010;Zhang et al, 2013) or land applied animal manure (Zilles et al, 2005;Pei et al, 2006;Heuer et al, 2011;Joy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Waste streams from hospitals, animal husbandry, and pharmaceutical production facilities contain elevated concentrations of antimicrobials (Campagnolo et al, 2002;Kummerer, 2001;Zilles et al, 2005) and are commonly treated in systems that rely on biological processes. Acceptable treatment performance has been reported in anaerobic lagoons treating manure with concentrations of antimicrobials that would inhibit sensitive microorganisms (Jindal et al, 2006;Zilles et al, 2005), but the mechanism(s) for maintaining biological activity in the presence of antimicrobials and the associated questions of how and when antimicrobial resistance develops are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Not only variation in doses (a function of dosage and body weight) and excretion factors, dilution, degradation, slurry application rates and soil variability, but also factors such as representative sampling in slurry and soil, and field residue history, complicate the validation of this part of the model. A recent study from the USA confirms this conclusion (Zilles et al, 2005). It can be concluded that slurry or nutrient concentrations should be related to a realistic time frame in which the contaminated slurry is produced and diluted in order to optimise the worst case predictions; the available field data do not allow for validation of the parameter selection in the models; and that field concentrations may vary a factor 30 within one field.…”
Section: Discussionmentioning
confidence: 99%